A wikification prediction model based on the combination of latent, dyadic and monadic features - Ferreira, Raoni Simões (2016)
Most of the reference information, nowadays, is found in repositories of documents semantically linked, created in a collaborative fashion and freely available in the web. Among the many problems faced by content providers in these repositories, one of the most important is Wikification, that is, the placement of links in the articles. These links have to support user navigation and should provide a deeper semantic interpretation of the content. Wikification is a hard task since the continuous growth of such repositories makes it increasingly demanding for editors. As consequence, they have their focus shifted from content creation, which should be their main objective. This has motivated the design of automatic Wikification tools which, traditionally, address two distinct problems: (a) how to identify which words (or phrases) in an article should be selected as anchors and (b) how to determine to which article the link, associated with the anchor, should point. Most of the methods in literature that address these problems are based on machine learning approaches which attempt to capture, through statistical features, characteristics of the concepts and its associations. Although these strategies handle the repository as a graph of concepts, normally they take limited advantage of the topological structure of this graph, as they describe it by means of human-engineered link statistical features. Despite the effectiveness of these machine learning methods, better models should take full advantage of the information topology if they describe it by means of data-oriented approaches such as matrix factorization. This indeed has been successfully done in other domains, such as movie recommendation. In this work, we fill this gap, proposing a wikification prediction model that combines the strengths of traditional predictors based on statistical features with a latent component which models the concept graph topology by means of matrix factorization. By comparing our model with a state-of-the-art wikification method, using a sample of Wikipedia articles, we obtained a gain up to 13% in F1 metric. We also provide a comprehensive analysis of the model performance showing the importance of the latent predictor component and the attributes derived from the associations between the concepts. The study still includes the analysis of the impact of ambiguous concepts, which allows us to conclude the model is resilient to ambiguity, even though does not include any explicitly disambiguation phase. We finally study the impact of selecting training samples from specific content quality classes, an information that is available in some respositories, such as Wikipedia. We empirically shown that the quality of the training samples impact on precision and overlinking, when comparing training performed using random quality samples versus high quality samples.